The Effect of Teaching Exercises Using Inquiry - based Learning on Mental Toughness and Learning Scoring Accuracy in Handball for Forth Stage Preparatory School Students - hamdan, Abdullah Ghazi (Journal of Physical Education, 2023)
The study aimed at designing teaching exercises using inquiry – based learning in handball as well as identifying the effects of these exercises on mental toughness and learning scoring accuracy in handball for fourth grade preparatory school students. The researcher noticed that learners who perform continuous skills during the application phase of class need mental toughness so as to increase students’ interaction with the traditional teaching material.  The researcher used the experimental method on (40) fourth stage preparatory school students from 2nd Al Kurkh education / Baghdad governorate for the academic season (2022 – 2023). The experiment was applied for (4) weeks then the data was collected and treated using SPSS to conclude that exercises using inquiry- based learning is suitable to fourth stage preparatory school students in handball lesson, they improve their mental toughness as well as scouring accuracy in handball. Finally, the researcher recommended developing the mental aspect during physical education class due to its positive role in skill learning.